Empowering small and medium enterprises (SMES) to foster balanced development in Asean: Insights and implications for Vietnam - Thanh, Tran Thi Mai; Linh, Tran Huong; Thuy, Tran Thu; Mai, Mai Thi Thanh; Dung, Tran Viet (Edelweiss Applied Science and Technology, 2025)
In the diverse and dynamic ASEAN landscape, this paper explores how small and medium enterprises (SMEs) internationalization can foster balanced regional development, focusing particularly on Vietnam. Employing a comprehensive approach, it investigates key enablers of SME international trade—namely, integration into Global Value Chains (GVCs), the implications of non-tariff barriers, and the transformative influence of e-commerce solutions. The findings underscore that while SMEs hold significant potential for stimulating economic diversification and equitable growth, they face intricate challenges ranging from regulatory complexity to constrained digital infrastructure. To address these hurdles, the research proposes targeted trade-based policies at both regional and national levels, aiming to unlock SMEs’ full internationalization potential. By doing so, it seeks to contribute substantially to a more equitable and sustainable development path, where ASEAN as a whole—and Vietnam as a compelling case study—demonstrate how strategic policy interventions and technological advancements can catalyze SME-led growth. Ultimately, these insights highlight the critical importance of SME internationalization in shaping ASEAN’s future economic landscape.